Among participation and political will. Popular initiative and the draft bill for water integrated resource management “ley de gestión integral del recurso hídrico” in Costa Rica - Abarca, Rocío (2014)
This article analyzes the political process and organizational context of discussion and struggle for new spaces of political participation in democratic regimes through direct democracy mechanisms such as the popular initiative, with the approach to the topic of citizen participation in the legislative in Costa Rica. Citizen Legislative Initiative is a recent addition in the Latin American constitutions and political practices. In our country, the law Nº8491 was issued on March 9 2006, the product of a constitutional reform which incorporated the terms “popular”, “participatory” and “people”, which led to legislative debate about the meaning of new political practices and legislative discussions about it.